Efektivitas Media Chromebook untuk Meningkatkan Hasil Belajar Peserta didik - Isnaini Maharani; Muhammad Isnaini; Imam Tauhid (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
In an increasingly advanced digital era, quality education is the main foundation in creating a superior next generation and the utilization of technology in learning is becoming increasingly essential. One of them is using Chromebook media that can help teachers in improving student learning outcomes and overall learning quality. This study aims to evaluate the effectiveness of using Chromebook media in improving student learning outcomes, analyze the differences in student learning outcomes before and after the use of Chromebook and identify the factors that influence the use of Chromebook in the learning process at Taman Musi Banyuasin Junior High School, especially in PAI subjects. The method used was descriptive with a quantitative approach, involving 57 students in grades VIII and IX as samples. The use of Chromebooks was proven to improve student learning outcomes with the average student score increasing to 68.28% with the percentage of student success increasing from 31.5% before use to 92.9% afterwards. The findings show that Chromebook media is effective in improving student engagement and understanding. The influencing factors are interactive teaching methods, access to diverse learning resources, and teachers' ability to manage learning. The integration of Chromebooks in the teaching-learning process improves student learning outcomes and it is important to develop the utilization of technology to achieve optimal educational outcomes.